Bibliometric Analysis of Sustainable Architecture in Indonesia - Nahak, Albertus; Poerwoningsih, Dina; Tutuko, Pindo (Proceedings of International Conference of Graduate School on Sustainability, 2022)
Sustainable architecture, also known as green architecture, is a good solution to maintain environmental impacts due to development, by paying attention to sustainability, materials, materials, energy, and ecosystems for future generations in line with the goals of the Sustainable Development Goals (SDGs). The purpose of writing this article is to analyze various articles from international-based scientific publications, namely "Elsevier" with keywords or topics about "sustainable architecture" in Indonesia. The method of writing this article uses bibliometric analysis to describe quantitative data from international studies related to the topic of sustainable architecture in Indonesia. The technique of collecting data from Elsevier is by setting the search term "Sustainable Architecture" and then determining the publication period for 2012-2022. The study instruments are (1) trends publications in 2012-2022; (2) type of publication; (3) core journals in international publications; (4) subject area of study; (5) mapping of study themes based on keywords and authors; (6) study productivity; and (7) distribution regional by author. The results of the analysis of the percentage of publications per year show that the issue of sustainable architecture in Indonesia has received enough attention from local and international academics. Academic attention to the topic is very high with a high intention and desire to publish their findings in an international journal scale. The best approach in the study of sustainable architecture is to pay attention to social, environmental, artistic, and humanities aspects. Keywords: Sustainable architecture; SDGs; Indonesia; Publication; Bibliometrics.